Improving Critical Thinking Ability and Learning Achievement through Discovery Learning - Putri, Afrindanti Sadiyah; Bintaro, Tri Yuliansyah (Jurnal Gentala Pendidikan Dasar, 2026)
This study was motivated by the low critical thinking ability and learning achievement of fourth-grade students in Science and Social Studies at SD Negeri 1 Wanogara Kulon. The purpose of this study was to determine the improvement of students’ critical thinking ability and learning achievement through the implementation of the Discovery Learning model assisted by animated audio-visual media. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of two cycles involving 20 students. Data were collected through observation and tests and analyzed using descriptive quantitative techniques. The results showed that student activity increased from 60% in Cycle I to 70% in Cycle II, while teacher activity improved from 50%–60% to 70%–80%. Students’ critical thinking ability, measured through the combined results of observation and critical thinking tests, improved from 60% in Cycle I to 75% in Cycle II. Furthermore, students’ learning achievement increased from 70% to 75%. Therefore, the implementation of the Discovery Learning model assisted by animated audio-visual media was proven effective in improving students’ critical thinking ability and learning achievement in Science and Social Studies.